2017
DOI: 10.18632/oncotarget.17374
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of transglutaminase 2 in non-small cell lung cancer patients

Abstract: Transglutaminase 2 (TG2) plays important roles in cell survival and cancer progression. In this study, we examined TG2 expression in specimen of 194 patients diagnosed with non-small cell lung cancer (NSCLC), and found that the TG2 gene expression was significantly higher in lung cancer tissues as compared to paired incisal marginal tissues or normal tissues. Our data revealed that patients with lower level of TG2 expression detected in cancer tissues had longer disease free survival and overall survival as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
1
6
0
1
Order By: Relevance
“…Two independent studies of non‐small cell lung cancer patients show that elevated TG2 level predicts disease recurrence and shorter disease free survival, and suggest that TG2 level may be a prognostic marker of disease progression . Moreover, in chemotherapy patients, progression free survival is lengthened if the patients have low tumor levels of TG2 .…”
Section: Tg2 In Tumor Typesmentioning
confidence: 99%
“…Two independent studies of non‐small cell lung cancer patients show that elevated TG2 level predicts disease recurrence and shorter disease free survival, and suggest that TG2 level may be a prognostic marker of disease progression . Moreover, in chemotherapy patients, progression free survival is lengthened if the patients have low tumor levels of TG2 .…”
Section: Tg2 In Tumor Typesmentioning
confidence: 99%
“… 16 , 17 Role of TG2 expression in inflammation induced carcinogenesis is well established in various cancers including ovary, colorectal, breast, renal and lung. 8 , 10 - 13 Its role in GBC has not yet been studied. Our study, comprising 100 patients of GBC and 28 patients of cholelithiasis (control group) is the first study to evaluate expression of TG2 in a large cohort of GBC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Chihong et al 13 have demonstrated the role of TG2 in cell survival and cancer progression in 194 patients diagnosed with non-small cell lung cancer (NSCLC) and found that TG2 expression was significantly higher in lung cancer tissues as compared to paired marginal tissues or normal tissues. They also postulated that patients with low TG2 expression levels had longer disease free survival and overall survival as compared those with higher TG2 expression and also found that high TG2 expression correlated with NSCLC recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These sections were then prepared for antigen retrieval in a citrate buffer with a pH of 6.0 by heating them in a microwave for 5-min cycles. The sections were then incubated overnight at a temperature of 4°C with a 1:200 diluted Anti-TG2 antibody (Abcam, USA), after which we incubated them with biotinlabeled Rabbit Anti-Mouse IgG H&L preabsorbed (Abcam, USA) for immunostaining (Chihong, et al, 2017).…”
Section: Lung Tissue Immunohistochemistrymentioning
confidence: 99%